MicroRNAs in Autoimmune Sjögren’s Syndrome - Seunghee Cha; Mahmoud Mona; Kyung Eun Lee; Dong Hee Kim; Kyudong Han (Genomics & Informatics)
MicroRNAs (miRNAs), small non-coding RNAs, have been implicated in various diseases and cellular functions as microregulators of gene expression. Although the history of miRNA investigation in autoimmune Sjögren’s syndrome (SjS) is fairly short, a substantial amount of data has already been accumulated. These findings clearly indicate potential clinical implications of miRNAs, such as autoantigen expression and autoantibody production, viral miRNAs regulating the calcium signaling pathway, and aberrant immune cell regulation and cytokine production. Research endeavors in the field are currently underway to select disease-specific diagnostic and prognostic biomarkers by utilizing different types of tissues or biological specimens of SjS patients. Various techniques for miRNA analysis with different stringencies have been applied, with the most recent one being next-generation sequencing. This review compiles and highlights differentially-expressed miRNAs in various samples collected from SjS patients and their potential implications in the pathogenesis of SjS. To facilitate the development of miRNA-targeted personalized therapy in the future, we urge more follow-up studies that confirm these findings and elucidate the immunopathological roles of differentially-expressed miRNAs. Furthermore, improved diagnostic criteria for the disease itself will minimize sampling errors in patient recruitment, preventing the generation of inconsistent data.